Change in PSNR According to Kvp, Mas and SID in CR System and DR System - Choi, Kyoungho; Young Jung, Jae; Ji Jung, Hyang; Jeong Heo, Eun; Kyu Ko, Jin; Keun Cho, Jung (International Journal of Engineering and Technology, 2018)
F/S System could not obtain the image valuable for diagnostics unless it was taken under the precise exposure condition according to the patient's somatotype but CR and DR systems can obtain good quality of image by the post-processing after obtain the image under sufficient exposure condition. However, it may expose the patient more than required as it can obtain the image not under the best condition. In this study, the results of assessing the chest images obtained by the changes in mAs, kVp and SID quantitatively represented high PSNR of SID 180 cm, 120 kVp and 3.2 mAs in common in the CR and DR systems. In DR system, the quality of image shows clear differences by the exposure condition depending on the presence of AEC. Particularly, since DR system has marginal condition that represents the difference if the quality of image is good or bad, the study on the optimum exposure condition should be made by equipment.Â